Failed Cartilaginous Grafts in the Eyelid: A Retrospective Clinicopathological Analysis of 5 Cases. Issue 5 (September 2016) - MacIntosh, Peter W.; Jakobiec, Frederick A.; Stagner, Anna; Rashid, Alia; Sutula, Francis C.; Yoon, Michael K.; Fay, Aaron M.
Abstract : Purpose: To analyze the clinical and histopathologic features of 5 failed autologous cartilaginous grafts to the lower eyelids and to analyze the reasons for these failures. Methods: In this retrospective case series, the data collected included patient ages, reasons for and duration of cartilaginous graft implants, sources of cartilaginous grafts, and clinical and histopathologic findings at time of graft removal using hematoxylin and eosin, elastic, Alcian blue, and Masson trichrome staining for analysis of tissue alterations. Results: Five cartilaginous, posterior lamellar lower eyelid grafts were complicated by eyelid thickening or retraction, graft extrusion, and entropion. Histopathologic findings included segmentation of the original single implant, stripped of its perichondrium, due to "kerfing, " sometimes with overlapping of the segments and scar formation between the segments. In place of the perichondrium that had been removed during the preparation the graft implants, a fibrous pseudoperichondrial capsule had formed. Pyknotic nuclei in varying degrees were typically found in the center of the grafts, despite a high degree of preservation of the extracellular matrix (collagenous, elastic, and proteoglycan components). No evidence of inflammation, cartilaginous vascularization, or necrosis was identified in any graft. Conclusion: Despite minimal reactive processes, kerfing (partial thickness cuts made in the graft to increase its pliancy) may be partially responsible for graft migration, deformation, and surgical failure. The consequences were graft fragmentation and overlapping of the multiple fragments. Graft migration can be exacerbated if a posterior lamellar graft is used to correct an anterior lamellar deficiency. Interference with the overall architectural integrity of the graft and its extracellular matrix appears to play no role in failure, despite removal of the perichondrium. Mild to moderate degrees of chondrocytic dropout in the absence of necrosis and inflammation are probably attributable to the thick and coarsely textured collagen of the fibrous pseudoperichondrial capsule that may impede diffusion of nutrients into the center of the graft. Abstract : Five failed cartilaginous grafts stripped of their perichondria to the lower eyelids appeared to be attributable mostly to kerfing or the inappropriate selection of the surgical procedure, despite excellent longstanding preservation of graft architecture.